2019
DOI: 10.1016/j.bbmt.2019.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical Transplantation with Post-Transplant Cyclophosphamide versus Unrelated Donor Hematopoietic Stem Cell Transplantation: A Systematic Review and Meta-Analysis

Abstract: Hematopoietic stem cell transplantation (HSCT) is the standard treatment for patients with high-risk hematologic malignancies. Only approximately 25% of siblings are HLA-matched, and thus alternative donors-unrelated or haploidentical-are usually the only options available. This meta-analysis aimed to compare haploidentical HSCT with post-transplantation cyclophosphamide and unrelated donor (URD) HSCT. We searched the PubMed and Cochrane databases for pertinent studies indexed between 2008 and 2018. Twenty obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Recently, Arcuri et al [37] performed a meta-analysis to compare clinical outcome of Haplo-SCT with MUD-SCT. They concluded that Haplo-SCT for hematologic malignancies achieved the same overall survival as MUD-SCT, with a lower incidence of GVHD and NRM, and advocated that Haplo-SCT with PTCy should strongly be considered as the first option for adult patients with hematologic malignancies who do not have matched sibling donors in experienced centers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Arcuri et al [37] performed a meta-analysis to compare clinical outcome of Haplo-SCT with MUD-SCT. They concluded that Haplo-SCT for hematologic malignancies achieved the same overall survival as MUD-SCT, with a lower incidence of GVHD and NRM, and advocated that Haplo-SCT with PTCy should strongly be considered as the first option for adult patients with hematologic malignancies who do not have matched sibling donors in experienced centers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, aGvHD incidence varies from 40% for HLA-identical siblings [6] to 80% for HLAmismatched unrelated donors [2,13]. Only approximately 25% of siblings are HLA-matched, and usually, the only alternatives are unrelated or haploidentical donors [39]. A recent study has reported that post-transplant cyclophosphamide in HLA-haploidentical HSCT is associated with low rates of severe graft-versus-host disease and its efficacy is comparable with HLA-matched HSCT [40].…”
Section: Discussionmentioning
confidence: 99%
“…Table S5 shows the number of patients with aGvHD for individual studies which report the grade and organs implicated (see Additional file, pp. [38][39][40]. Most of the included patients suffered grade III-IV (82.99%).…”
Section: Mesenchymal Stromal Cells For the Treatment Of Steroidrefracmentioning
confidence: 99%
“…acute/chronic graft-versus-host disease (GVHD) and nonrelapse mortality (NRM), particularly when the graft source is peripheral blood stem cells (PBSCs). 3,5,9,10 We and others have previously reported encouraging results with tacrolimus/sirolimus-based GVHD prophylaxis after MUD-HCT. 6,11,12 Results from our earlier single institution analysis of tacrolimus/sirolimus-based GVHD prophylaxis after MUD and MMUD HCT showed that relative to MUD, MMUD-HCT is associated with significantly lower overall survival (OS), primarily because of increased NRM associated with GVHD and infections.…”
Section: Introductionmentioning
confidence: 92%